Forecasting the Genetic Impacts of Net Pen Failures on Gulf of Mexico Cobia Populations Using Individual‐based Model Simulations. Issue 1 (4th July 2016) - Darden, Tanya L.; Robinson, John D.; Strand, Allan E.; Denson, Michael R.
Abstract: Offshore net pen fish farming provides a cost‐efficient means for production of marine finfish, and there is great interest in development of net pen operations in domestic waters. However, there are concerns over the possible genetic and ecological impacts that escaped fish may have on wild populations. We used individual‐based simulations, with parameter values informed by life history and genetic data, to investigate the short‐term (50 yr) impacts of net pen failures on the genetic composition of cobia, Rachycentron canadum, stocks in the Gulf of Mexico. Higher net pen failure rates resulted in greater genetic impacts on the wild population. Additionally, the use of more genetically differentiated source populations led to larger influxes of non‐native alleles and greater temporal genetic change in the population as a result of net pen failure. Our results highlight the importance of considering the appropriate source population for broodstock collection in net pen aquaculture systems and help to provide a general set of best management practices for broodstock selection and maintenance in net pen aquaculture operations. A thorough understanding of the genetic diversity, stock structure, and population demography of target species is important to determine the impact escapees can have on wild populations.